Pyrenochaetopsis huizeanum sp. nov. (Pyrenochaetopsidaceae, Pleosporales) from rocky desertification soil in Yunnan Province - Chen, Lai-Ping; Duan, Zhong-Wen; Zhagn, Xian-Kun; Zhan, Yu-Chen; Yu, Ze-Fen (Phytotaxa, 2025)
During a survey of soil fungi in rocky desertification regions of Yunnan Province, China, a novel species, Pyrenochaetopsis huizeanum, was isolated from nutrient-poor soils. Phylogenetic analyses using combined ITS, LSU, rpb2 and tub2 gene sequences clearly positioned the new species within the genus Pyrenochaetopsis. The novel taxon formed a distinct monophyletic lineage closely related to a group of six known species viz. P. kuksensis, P. musae, P. oryzicola, P. paucisetosa, P. botulispora and P. tabarestanensis. Morphologically, Pyrenochaetopsis huizeanum differs from P. musae, P. oryzicola and P. botulispora in having setae and larger pycnidia, from P. paucisetosa by having narrower conidia, from P. kuksensis by producing larger conidia, and from P. tabarestanensis by lacking chlamydospore. Here, we provide a detailed description, illustrations, and phylogenetic placement of the newly proposed species, Pyrenochaetopsis huizeanum.